Challenges of the Newtonian Paradigm for Management of Health Delivery System: A Perspective - Mohammad Zayandeh (Taṣvīr-i salāmat)
Despite the evident shortcomings of the Newtonian paradigm, it remains the intellectual, scientific, and practical foundation for many disciplines. This paradigm adopts a reductionist approach, where understanding the entire system hinges on understanding its constituent parts. For managers and organizational leaders, differentiating between simple, complicated, and complex systems, and recognizing their distinct characteristics, is vital for enhancing both efficiency and effectiveness. The complex healthcare delivery system is often managed as a simple or complicated system. Managers mistakenly apply rigid guidelines and inflexible programs—principles more suited to simpler systems—to the healthcare system. This results in certain essential aspects being overlooked, such as the interaction between various components and their interrelationships, which are key characteristics of complex systems. Focusing on these interactions could lead to increased sustainability, efficiency, and effectiveness. Complex systems require decentralized control rather than central command. They are shaped by their historical context, thrive on the edge of order and chaos, and their components may not always have a complete understanding of the larger system. Moreover, complex systems are notably responsive to feedback.